Liberal globalization or global imperialism? Five pieces to put together the puzzle of the present - Coronil, Fernando (2016)
The author explores how the events of September 11, 2001 have changed the global configuration of power. As a way of comparison, the author describes past manifestations of imperialism as terrorist forms practiced from the Metropoli versus new manifestations that rather take the form of private terrorism or terrorism against the USA. The author tracks the usage, utility and decline of the concept of “imperialism” and suggests the utility of the concept of the “power of coloniality”, for understanding the colonial, national, and global modalities of imperialism. Finally and in dialogue with Subcomandante Marcos, the author identifies and describes the five pieces of the puzzle of current global imperialism.